If You Don't Know Me by Now: Explaining Local Candidate Recognition - Heiko Giebler; Bernhard Weßels (German Politics, 2017)
For the personal vote to be cast in a meaningful way it is a minimal condition that voters recognise candidates. However, from earlier studies we know that there is huge variation in the number of candidates recognised. Little to nothing is known about candidate recognition and its determinants. This study explores the sources of candidate recognition from three different angles: candidates; citizens; and context. Furthermore, it enables the distinction of campaign-related from other factors. A unique multi-level within-subject design was set up for the analyses of the 2013 German Federal Election to ensure a meaningful validation of our theoretical framework. Our results suggest that, indeed, many factors lead to recognition but as well that earlier studies overestimated the effects of political interest or incumbency status. Moreover, we show that a good campaign makes a difference for recognition – as does the context in which it takes place.
Keywords: 330